Functional association between telomeres, oxidation and mitochondria - Moustakli, Efthalia; Zikopoulos, Athanasios; Sakaloglou, Prodromos; Bouba, Ioanna; Sofikitis, Nikolaos; Georgiou, Ioannis (Frontiers in Reproductive Health, 2023)
Prior research has substantiated the vital role of telomeres in human fertility. Telomeres are prerequisites for maintaining the integrity of chromosomes by preventing the loss of genetic material following replication events. Little is known about the association between sperm telomere length and mitochondrial capacity involving its structure and functions. Mitochondria are structurally and functionally distinct organelles that are located on the spermatozoon's midpiece. Mitochondria produce adenosine triphosphate (ATP) through oxidative phosphorylation (OXPHOS), which is necessary for sperm motility and generate reactive oxygen species (ROS). While a moderate concentration of ROS is critical for egg—sperm fusion, and fertilization, excessive ROS generation is primarily related to telomere shortening, sperm DNA fragmentation, and alterations in the methylation pattern leading to male infertility. This review aims to highlight the functional connection between mitochondria biogenesis and telomere length in male infertility, as mitochondrial lesions have a damaging impact on telomere length, leading both to telomere lengthening and reprogramming of mitochondrial biosynthesis. Furthermore, it aims to shed light on how both inositol and antioxidants can positively affect male fertility.